2017
DOI: 10.5487/tr.2017.33.2.157
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Caffeine on the Long Bones and Testes in Immature and Young Adult Rats

Abstract: This study was to evaluate the age-dependent effects of caffeine exposure on the long bones and reproductive organs using male rats. A total of 15 immature male rats and 15 young adult male rats were allocated randomly to three groups: a control group and two groups fed caffeine with 120 and 180 mg/kg/day for 4 weeks. Exposure to caffeine at either dose significantly reduced body weight gain; a proportional reduction in muscle and fat mass in immature animals, whereas a selective reduction in fat mass with rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…Even so, our findings of no significant difference in body weight are consistent with previous reports of similar lean body mass, total body fat, bone weight, and length in caffeine‐treated adult rats compared with controls (Kwak et al. ).…”
Section: Resultssupporting
confidence: 93%
“…Even so, our findings of no significant difference in body weight are consistent with previous reports of similar lean body mass, total body fat, bone weight, and length in caffeine‐treated adult rats compared with controls (Kwak et al. ).…”
Section: Resultssupporting
confidence: 93%
“…Exposure to EDCs in puberty may consequently cause long-term and more serious damage to the male reproductive system compared with adults. For example, caffeine exposure reduces the size and absolute weight of the testes more significantly in immature rats than adults (Kwak et al, 2017). The deteriorative effects of ethanol on gonadal activity are also more lethal in puberty than in adults (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…16 Other studies conducted by Ayoub N et al in February 2016, Yoojin et al in April 2017, and Schuchwsky E et al in December 2017 suggested no significant weight gain or loss with the use of energy drinks on rats. 17,18,19 No considerable weight change with energy drink due to stimulation of fat oxidation and thermogenic activity because caffeine has the capability to impede the phosphodiesterase-induced breakdown of cAMP (intracellular cyclic adenosine monophosphate) and caffeine's antagonism of adenosine on increased norepinephrine release which is responsible for weight control up to some extent. But contrary to the above results, Fahad in his study, related to energy drink effects on albino Wister rats, reported energy drink given for 21 days significantly reduce body weight.…”
Section: Discussionmentioning
confidence: 99%